A STUDY ON SOCIAL WELFARE ACTIVITIES BY TWENTY 20 ORGANISATION, A CSR INITIATIVE OF KITEX, TOWARDS KIZHAKKAMBALAM PANCHAYAT - Dr.Tinsy Rose Tom (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2022)
Introduction: Corporate Social Responsibility is a tool in the modern world for enhancing the confidence of corporate sector with its related external environment society. By practicing Corporate Social Responsibility, also called corporate citizenship, companies can be conscious of the kind of impact they are having on all aspects of society, including economic, social and environmental. Objectives: The study seeks to assess the level of awareness about the CSR activities among the respondents of the Kizhakambalam panchayat, to study the CSR activities and its impact on the community and to examine whether the respondents are satisfied with the CSR initiatives of the Kitex. Methodology: The population of study comprises of people residing in Kizhakambalam Panchayat.The determination of sample size means the number of elements of the population to be taken. Here the sample size is 50 respondents. This study based on both primary and secondary data. The primary data is collected with the help of structured questionnaire. While secondary data is collected with the help of various books, journal, articles, company website etc. Data analysis has been done by using appropriate statistical and mathematical tools, such as percentages, simple average etc. Findings: kitex group in kizhakkambalam panchayat improved the standard of living of the beneficiaries. Twenty 20 activities of kitex provides financial and non financial support to the society. They also ensures that the benefit of social welfare activities are reached to all level of the society in kizhakkambalam panchayat. Keywords: CSR,Social Welfare